Digitalization in a resource-extracting region: from cluster to business ecosystem - Zhernov Evgeny (EDP Sciences, 2021)
The purpose of the study is to trace the evolution of the mineral resource cluster in a resource-extracting region from a territorial association of entities in the industrial economy to a business ecosystem in the digital economy within the framework of the sustainable development concept. The urgency of the research is due to the increase in the information and knowledge intensity of a product in the digital economy, which makes the cluster policy based on the digital principle more efficient than that based on the territorial principle. The digitalization of the mineral resource sector of a resource-extracting region, started with a cluster - a progressive organizational and managerial form - is seen by the authors as a strategic means of increasing the sustainability and efficiency of the socio-economic development of a region. The delegation of responsibility for the modernization of the economy to the regional level gives particular importance to regional research. The dependence on the state of the world market of fuel and energy resources, the exhaustion of the mainly raw material export model of economic growth put Kuzbass, the mining region of Western Siberia, in the most difficult situation. The issue of accelerating the transition to an innovation resource type of development through structural and technological transformation in the context of the general course towards digitalization is urgent for it. A theoretical substantiation of the necessity, possibility and feasibility of digitalization of the mineral resource cluster as a factor in the sustainable development of a resource extracting region is presented in the article.